The Useful Conclusion in our Experience Regarding the Sacral Injection - Sayed Issa, Abdulhamid (Journal of Spine and Neuroscience, 2024)
Caudal injection is a type of epidural injection that is administered to the lower back to reduce pain and inflammation. The injection contains a steroid medication that is injected into the lower part of the epidural space, which surrounds the nerve roots in the lower back. The procedure is usually performed on an outpatient basis, and most patients experience relief from back pain within a few days. The sacral injection is another name for a caudal epidural injection. It is a type of spinal epidural injection that is administered to the sacral hiatus, which is the opening at the base of the spine near the tailbone. The injection is used to treat nerve pain and inflammation caused by conditions such as spinal canal stenosis, herniated disks, degenerative disk disease, sciatica, or radiculopathy.
Keywords: Caudal Injection; Sacral Injection; Epidural Injection; Steroid; Back Pain